Supply Chain Complexity in the Semiconductor Industry: Assessment from System View and the Impact of Changes. Issue 3 (2015) - Sun, Can; Rose, Thomas
Abstract: The semiconductor industry is considered to be one of the most complex industries, not only due to more than 500 processing steps involved in the manufacturing and various products, but also the harsh environment it faces, e.g., the volatile electronic market and the unpredictable demand. On the one hand, companies have to adapt their behaviors to the changing environment; on the other hand, many changes inevitably bring in the complexities and challenges to the supply chain management. Our research strategy is to build a general model for complex systems first and then generate the supply chain instance model from it. A complex system can be decomposed into three levels: subsystem, component and part. The part level is the lowest level which defines four types of key elements (process, role, object and its states) and different relationships among each other. Various types of complexity are discussed, and changes and their potential impact on the system complexity are also analyzed. We use an instance model from the semiconductor supply chain to illustrate the system modeling, specify the features of each element on the part level and propose the metrics of complexity measurement. Consequently, two scenarios are compared by calculating the variation of their overall complexity. The intermediate results of doctoral research are presented and the future research is also planned.